Learn Objective-C on the Mac - Dalrymple, Mark (Apress, 2012)
One of the dangers of being a programmer for a long time is that you can lose that spark of delight that got you interested in programming the first place. Luckily, shiny new technologies come along all the time that can reignite that interest, and Mac OS X is chock full of shiny stuff. Objective-C is a programming language that blends C’s speed and ubiquity with an elegant object-oriented environment and provides a buzzword-laden cornucopia of programming good times. Objective-C is the gateway drug for many of Apple’s niftiest technologies, such as the Cocoa toolkit and the iPhone SDK. Once you’ve mastered the Objective-C language, you’re well on your way to conquering the rest of the platform. And from there, you can try to take over the world